Construction and structural adhesives and sealants : an industrial guide - Flick, Ernest W. (Noyes Publications, 1988)
This book describes more than 1600 construction and structural adhesives and sealants currently available from over 100 suppliers. These adhesives and sealants can be used for major construction and structural applications as well as in commercial businesses, schools, and offices, and by the home-repair handyman. The products can be applied to such diverse materials as concrete, ceramics, vinyl, polyethylene, foamed plastics, wood, plywood, fiberboard, gypsum board, prefinished panels, leather, and cotton.